The Violation of Cooperative Principle Done by Joni Mitchell in the Elton John’s Interview - Darmika, Andi Muhammad Trisna Yudi; Juanda, Juanda; Supriadi, Asep (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2024)
This study is aim to identify the violation of cooperative principle done by Joni Mitchell in the interview with Elton John on his show, Rocket Hour. The violation of cooperative principles occurs when speaker intentionally or unintentionally do not obey the rule of the four maxims. The four maxims are maxim of quantity, maxim of quality, maxim of relevance, and maxim of manner. The data is taken from the transcription of the interview done by Joni Mitchell in an Elton John show called Rocket Hour in which occurred in 2022. The result reveals that out of the four maxims, Joni Mitchell violated maxims of quantity the most throughout the interview with 3 data, while the other maxims had only been violated once each. Keywords: Cooperative Principles, Maxim violation, Joni Mitchell, Elton John